Cinema psychology: universes of realities, dreams and meanings - Montero López, Víctor Eusebio (2020)
A psychosocial analysis of cinema, both as mass media and in relation to its effects on the spectator and society, is carried out. Aspects to be considered for an integral analysis of the films are thus indicated.